ASSESSMENT OF EFFICIENCY OF ENTERPRISE MARKETING COMMODITY POLICY - Gontareva, Irina; Mangushev, Dmitry; Zhdenovska, Alina (Social Economics, 2020)
Marketing is the way in which an enterprise achieves its goals. An important tool for marketing activities of the enterprise is product policy. The economic importance lies in the fact that skillful management of marketing product policy will allow the company to survive in conditions of fierce competition and become an effective enterprise. From the social point of view, assortment management shapes consumers 'tastes, generates needs, and vice versa, consumers' tastes and needs greatly influence marketing product policy.The purpose of the study is to substantiate the effectiveness of the evaluation of marketing product policy of the enterprise.It is determined that when making decisions about expanding and reducing the product range it is necessary to monitor changes in external (level of competition, demand, product life cycle) and internal (financial and economic) indicators that determine the effectiveness of marketing product policy, both before and after decision.It is substantiated that the indicators that in addition to their direct purpose can also be used to address the expansion, as well as reduction of product range include: revenue from sales of goods and services, profit, profitability, turnover, marginal revenue and product competitiveness. Methods for determining the partial and integrated indicator for assessing the effectiveness of marketing product policy of the enterprise is proposed, the features of application for different types of economic activity are highlighted.The defined list of indicators is not exhaustive. There are a number of indicators, factors that can influence decisions on removal or inclusion of commodity positions in the assortment policy of the enterprise. Situational analysis of the composition of indicators will be the direction of further research.